Identifikasi Penerapan Unsur-Unsur Iconic Jawa pada Bangunan Hotel di Surakarta - Anita Dianingrum; Titis Srimuda Pitana; Maya Andria Nirawati; Mohamad Muqoffa; Pratiwi Anjar Sari (Universitas Sebelas Maret Surakarta, 2021)
City branding is an effort to build an identity about a city and providing opportunities for the realization of regional development both in terms of economy and tourism. Branding can be realized through all forms of parts of the city that have distinctive characteristics that are influenced by physical and non-physical characteristics. “Solo the Spirit of Java” means that “Solo is the soul of Java” which reflects the depth of meaning of the cultural, artistic and historical roots of Solo. Since branding was established and legalized, several things have been done by the city government, one of the efforts are regarding physical characteristics is clearly visible in several buildings including cultural heritage buildings. Javanese iconic elements are deliberately preserved as a form of preservation and branding. This research was conducted to identify the application of Javanese iconic elements in hotel buildings in Surakarta. The method used in this study is collecting secondary data and observing to identify the application of Javanese iconic elements in buildings. The results illustrate that the application of Javanese iconic elements in hotel buildings is not optimal. It is because the visual view of building has not been able to attract attention, so it does not have a strong character. This needs more attention to all relevant stakeholders to improve the image or character of the building so that it can become a city branding that can strengthen the identity of Surakarta City through physical characteristics.